Conference Review: Symposium on ‘Peacebuilding, the Arts and the Participation of Children and Young People’, Queen’s University Belfast, 2024 - Lamb, Edel (Irish Journal of Arts Management and Cultural Policy, 2025)
In March 2024 the Senator George J. Mitchell Institute for Global Peace, Security and Justice at Queen’s University Belfast hosted a symposium on ‘Peacebuilding, the Arts and the Participation of Children and Young People’. The event, which ran in conjunction with Young at Art’s Belfast Children’s Festival, brought together practitioners and researchers to explore the role of the arts in facilitating the expression of children and young people and the contribution this can make to peacebuilding, historically, now and in the future. This review outlines the key themes that emerged during the symposium, which include the rights of children and young people, the significance of the creative arts as a mode of expression, the conditions for children and young people’s contribution to peacebuilding and the challenges for collaboration: both intergenerational and inter-sectoral.